Designing Adaptive Artificial Intelligence to Integrate 21st Century Competencies into Islamic curricula (Contrarius Series: Law & Social Justice, 2026)
Traditional Islamic curricula often emphasize religious knowledge while underrepresenting competencies, which is important for thriving in the 21st century. This phenomenon creates a tension between religious aims and contemporary educational demands. This qualitative study explores how adaptive artificial intelligence (AI) tools can be designed and integrated to support holistic student development within a traditional madrasah setting. Using a multiple-case, design-based qualitative approach, data were collected through semi-structured interviews (n=18), focus groups (n=5), classroom observations, and curriculum documents across four institutions in Malaysia and Cambodia. Findings make four themes relatively: (1) alignment tensions between religious epistemologies and competencies, (2) flexible opportunities for skills development, (3) pedagogical redesign requirements such as teacher roles, assessment, and learning pathways, and (4) ethical, cultural, and infrastructural constraints shaping uptake. Participants emphasised adaptive AI’s potential to scaffold critical thinking, collaboration, and values-based decision-making when technologies are co-designed with scholars and teachers. However, success depends on careful value alignment, transparent algorithms, professional development, and contextualized assessment practices. The study concludes that adaptive AI can bridge traditional Islamic education and 21st-century competencies when being guided by a responsive design culture and government participation. It will significantly offer a scalable pathway to holistic student development and policy recommendations for curriculum reform.